2019
DOI: 10.3390/w11051064
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Drought Risk Assessment in Southwest China

Abstract: Drought disasters jeopardize agricultural production and are expected to become more serious in the context of global climate change. However, in China, little attention has been paid to evaluating agricultural drought risk in humid areas (such as in Southwest China), which have also been affected by severe drought in recent years. In this work, we used the Standardized Precipitation Evapotranspiration Index (SPEI), which was computed from high-quality monthly precipitation and temperature data from 92 rain-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 54 publications
(88 reference statements)
0
48
0
1
Order By: Relevance
“…As the drought continued to develop, the correlation coefficient became lower. Zeng ZQ et al concluded that the main meteorological reason for the high frequency of extreme drought was the combined effect of abnormal decreases in rainfall and continued increases in temperature [29]. Wang HJ et al indicated that drought in China was mainly concentrated around the changes in light and moderate drought and wind speed, precipitation, temperature were the most sensitive variable in northwest China, while in south China it was precipitation, followed by wind speed, temperature, relative humidity, and sunshine duration [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the drought continued to develop, the correlation coefficient became lower. Zeng ZQ et al concluded that the main meteorological reason for the high frequency of extreme drought was the combined effect of abnormal decreases in rainfall and continued increases in temperature [29]. Wang HJ et al indicated that drought in China was mainly concentrated around the changes in light and moderate drought and wind speed, precipitation, temperature were the most sensitive variable in northwest China, while in south China it was precipitation, followed by wind speed, temperature, relative humidity, and sunshine duration [44].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increasing trend that emphasizes the combined role of drought hazard and drought vulnerability to conduct a risk assessment. For example, Zeng et al assessed agricultural drought risk by combining the role of drought hazard (calculated by the intensity and frequency of drought) and agricultural drought vulnerability in southwest China [29]. David et al presented a method for obtaining indices and maps of vulnerability to drought in Mexico; indices and maps were based on a set of socioeconomic and environmental indicators [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPEI runs at a monthly time step and requires the monthly P and PET as inputs. Similar to SPI, the SPEI must be associated with a specific timescale to reflect the impact of previous water deficits on current drought status [19,21,23,24]. The term drought timescale refers to the time lag that typically exists between the start of water shortage and the identification of its consequences [32].…”
Section: Calculation Of Spei and Syrsmentioning
confidence: 99%
“…Here, we only focus on the assessment of agricultural drought risk. Some studies have evaluated agricultural drought risk in China [23][24][25]. These studies provide valuable insights into where agricultural production is more likely to be affected.…”
Section: Introductionmentioning
confidence: 99%